A Low Power Sub-μW Chemical Gilbert Cell for ISFET Differential Reaction Monitoring - Kalofonou,M; Toumazou,C (IEEE Transactions on Biomedical Circuits and Systems, 2014)
This paper presents a low power current-mode method for monitoring differentially derived changes in pH from ion-sensitive field-effect transistor (ISFET) sensors, by adopting the Chemical Gilbert Cell. The fabricated system, with only a few transistors, achieves differential measurements and therefore drift minimisation of continuously recorded pH signals obtained from biochemical reactions such as DNA amplification in addition to combined gain tunability using only a single current. Experimental results are presented, demonstrating the capabilities of the front-end at a microscopic level through integration in a lab-on-chip (LoC) setup combining a microfluidic assembly, suitable for applications that require differential monitoring in small volumes, such as DNA detection where more than one gene needs to be studied. The system was designed and fabricated in a typical 0.35 μm CMOS process with the resulting topology achieving good differential pH sensitivity with a measured low power consumption of only 165 nW due to weak inversion operation. A tunable gain is demonstrated with results confirming 15.56 dB gain at 20 nA of ISFET bias current and drift reduction of up to 100 times compared to a single-ended measurement is also reported due to the differential current output, making it ideal for robust, low-power chemical measurement.